2018
DOI: 10.1136/jech-2018-210745
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic correlates of eating disorder subtypes among men and women in France, with a focus on age

Abstract: BackgroundOn the population level, the association of age and other sociodemographic factors with eating disorders (ED) is unclear.MethodsWe used cross-sectional data from the French general population-based NutriNet-Santé e-cohort (n=49 603 adults; 76.3% women; mean age=50.4±14.6 years). ED were evaluated in 2014 with the 5-item SCOFF screening questionnaire and the Expali algorithmic tool. Likely cases of restrictive, bulimic, hyperphagic and other ED were the dependent variables. Age, marital status, educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…The level of education predicted smoking only in women with AN. This finding is consistent with the literature, which associates low educational levels with higher levels of smoking in EDs (68), other psychiatric conditions (77,78), and even in healthy individuals (71).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The level of education predicted smoking only in women with AN. This finding is consistent with the literature, which associates low educational levels with higher levels of smoking in EDs (68), other psychiatric conditions (77,78), and even in healthy individuals (71).…”
Section: Discussionsupporting
confidence: 93%
“…Age seems to be a key factor in EDs. Among men and women, age demonstrates inverse linear associations with both restrictive and bulimic EDs, highlighting 18-25 years as the most vulnerable period (68). Age is also an important variable that correlates with several personality traits and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of prevalence, the population included is fairly representative of the usual clinical population, with R, B, and C patients accounting for 29%, 10%, and 61% of the recruitment. The C disorders prevail over R and B in accordance with previous prevalence studies, and this case mix is close to the estimation of the prevalence of ED in France [31]. Most interestingly, all these patients were included before the initiation of care in the Rouen University Hospital, and may thus be considered as "naive" patients, which prevents from bias related to previous therapeutic interventions.…”
Section: Discussionsupporting
confidence: 81%
“…A recent literature review indicated that binge eating, then bulimia nervosa and anorexia nervosa, had the highest lifetime prevalences [2]. College years coincide with the typical age of onset for EDs [3,4], and it is well-documented that EDs are a significant concern among college students [5,6] with a higher risk of restrictive EDs [7]. College years fall into a crucial developmental phase, known as "emerging adulthood" [8].…”
Section: Introductionmentioning
confidence: 99%